David Brown's Divine Humanity. Issue 1 (9th January 2015) - Tanner, Kathryn
<x content-type="archive" xml:space="preserve">Abstract</x> The contributions of this fine book are many but I will concentrate on three, before turning to several more critical remarks. First, and most obviously, the book does the invaluable service of surveying developments in kenotic christology in the nineteenth century while situating them nicely in their different contexts of origin and with reference to lines of mutual influence: continental, Scottish and British trends are all canvassed rather masterfully. Some attention, in lesser detail, is also given to the way these christological trends are extended in the twentieth century to accounts of the Trinity and God's relation to the world generally: kenosis, the self-emptying or self-limiting action of God, in the incarnation, is now viewed as a primary indication of who God is and how God works, from creation to salvation.